2009
DOI: 10.1080/09553000902748583
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of organic and inorganic germanium compounds in cellular radiosensitivity and preparation of germanium nanoparticles as a radiosensitizer

Abstract: We demonstrated that inorganic but not organic germanium compounds exerted radiosensitizing effect in cells. Nanometer-sized germanium particles were fabricated and were able to enhance the radiosensitivity of cells. Confounding effect may occur when comet assay is used to estimate the level of DNA damage in the presence of germanium nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…27) Previous studies indicate that Ge-132 is nontoxic to CHO-K1 cells, 28) and we also confirm that Ge-132 has no toxicity on CHO-K1, HeLa, and SH-SY5Y cells in our LDH assay. Notably, we show here that Ge-132 has a cell proliferative effect, as evident from the increase in intracellular ATP content in cultured cells.…”
Section: Discussionsupporting
confidence: 72%
“…27) Previous studies indicate that Ge-132 is nontoxic to CHO-K1 cells, 28) and we also confirm that Ge-132 has no toxicity on CHO-K1, HeLa, and SH-SY5Y cells in our LDH assay. Notably, we show here that Ge-132 has a cell proliferative effect, as evident from the increase in intracellular ATP content in cultured cells.…”
Section: Discussionsupporting
confidence: 72%
“…Therefore, researchers are encouraged to assess the extent to which the concentration of CNPs remaining in the sample could influence the use of toxicity assays and, when possible, to use complimentary assays for an endpoint. Along these lines, it was recently shown that germanium NP attachment directly to DNA during the alkaline Comet assay procedure probably resulted in arbitrary DNA fragmentation, a determination made by observing apparent DNA damage to cells harvested immediately after the NP addition [115]. In addition, fullerene NPs have recently been shown to oxidize in the presence of sunlight, forming a currently not-well-defined set of byproducts [116,117].…”
Section: Potential Experimental Artifactsmentioning
confidence: 99%
“…The main concern for the interactions within the comet assay is that NPs have been observed in the ‘head’ of the comets during scoring (4), suggesting that these NPs were present during the assay performance. In principal, such NPs may, e.g., induce additional breaks in ‘naked DNA’ during the assay or may affect the migration of DNA under electrophoresis (3,5). Furthermore, oxidative stress caused by NPs may be underestimated if the NPs, or released ions, affect the Fpg (formamidopyrimidine-DNA glycosylase) enzyme used to detect oxidative DNA damage (6).…”
Section: Introductionmentioning
confidence: 99%